Penggunaan Video Interaktif sebagai Upaya Optimalisasi Edukasi Persiapan Operasi oleh Perawat Setting Rawat Jalan - Winesa, Tifanne; Afriyani, Tuti; Hariyati, Rr Tutik S; Sudaryati, Sudaryati; Nasri, Muhammad (Journal of Telenursing (JOTING), 2023)
This study aims to provide an overview of the obstacles to education on preparation for surgery for outpatients and alternative solutions to increase the effectiveness of offering education on preparation for surgery. The method is a survey with interviews, questionnaires, fishbone analysis, problem prioritization, implementation, and evaluation. The results showed that 60.7% of outpatient nurses involved in the study conducted surgery preparation education without specific media and guidance based only on general educational SOPs. Data shows that 46% of nurses need more time to provide education, and its implementation will not be optimal during busy hours. 28% of cases of surgical failure are caused by ineffective education on preparation for surgery. In conclusion, interactive video educational media makes it easier for nurses to implement instruction quickly. This impacts patients' ability to understand educational material more efficiently so that the surgical failure rate can be reduced. Keywords: Operation Preparation Education. Fishbone. Educational Media. Interactive Videos